2014
DOI: 10.1111/nep.12211
|View full text |Cite
|
Sign up to set email alerts
|

Treatments to slow progression of autosomal dominant polycystic kidney disease: systematic review and meta‐analysis of randomized trials

Abstract: These data suggest that somatostatin analogues and vasopressin receptor antagonists attenuate TKV increase. The neutral effects of TORC1 inhibitors on TKV could be true, or due to heterogeneity in study population, drug efficacy and follow-up duration. In the future, further well-designed and powered trials of longer duration using new biomarkers or therapeutic agents with better tolerance are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Using MRI-determined increases in kidney volume as a marker of disease progression, rapamycin-based regimens showed significantly reduced cystic kidney volumes when compared to alternative treatments [190,195,196]. Clinical trials using rapamycin to treat ADPKD have however produced varied results [197,198,199], though they may have been impeded by small sample size, reliance on poor markers of clinical progression, short follow up time for such a slow-progressing disease, and insufficient rapamycin doses [200]. …”
Section: Ageing and Age-related Pathologies Amenable To Treatment mentioning
confidence: 99%
“…Using MRI-determined increases in kidney volume as a marker of disease progression, rapamycin-based regimens showed significantly reduced cystic kidney volumes when compared to alternative treatments [190,195,196]. Clinical trials using rapamycin to treat ADPKD have however produced varied results [197,198,199], though they may have been impeded by small sample size, reliance on poor markers of clinical progression, short follow up time for such a slow-progressing disease, and insufficient rapamycin doses [200]. …”
Section: Ageing and Age-related Pathologies Amenable To Treatment mentioning
confidence: 99%
“…A recent meta-analysis confirmed the efficacy of SST analogues in reducing the progressive increase of TKV, on average with a reduction of 9% compared with the growth observed in patients treated with placebo or conventional therapies. However, treatment with SST analogues did not demonstrate significant effects on the eGFR (80). Based on these studies, in August 2015, European Medicines Agency (EMA) attributed to lanreotide the Orphan Drug designation for the treatment of ADPKD.…”
Section: Somatostatin Analoguesmentioning
confidence: 99%
“…A single trial (n ¼ 41) of eicosapentaenoic acid did not alter the progression of either total kidney volume or renal dysfunction. 49 Adverse events were significant for interventions in all trials compared to placebo. These data suggested that somatostatin analogues and AVP receptor antagonists attenuate total kidney volume increase.…”
Section: V2 Receptor Inhibitorsmentioning
confidence: 99%
“…These data suggested that somatostatin analogues and AVP receptor antagonists attenuate total kidney volume increase. 49 …”
Section: V2 Receptor Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation